2010
DOI: 10.1097/opx.0b013e3181d951df
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contact Lens Wear and a Near Task on Tear Film Break-Up

Abstract: During tasks requiring concentration, the IBI increased (blink rate decreased) and many blinks were incomplete without CLs. With CLs, tear film instability increased. Blinking frequency also increased, but it remained high when subjects played the game, and symptoms of ocular irritation increased. This suggests that wearing soft CLs, even when fully adapted, provides enough extrinsic ocular surface stimulation to override internal controls and affect blink parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 51 publications
4
66
0
Order By: Relevance
“…This study also indicated that LIPCOF and lid wiper epitheliopathy might be linked to CL-related meibomian gland atrophy. These associations may indicate that CLs could produce these negative effects on meibomian glands through mechanical interaction with the eyelids, 6 by altering the natural blink, 33 or through some other potential mechanism yet to be discovered. Although these regression analysis results are interesting, they show that if there is an association, it is likely not a straightforward one.…”
Section: Discussionmentioning
confidence: 98%
“…This study also indicated that LIPCOF and lid wiper epitheliopathy might be linked to CL-related meibomian gland atrophy. These associations may indicate that CLs could produce these negative effects on meibomian glands through mechanical interaction with the eyelids, 6 by altering the natural blink, 33 or through some other potential mechanism yet to be discovered. Although these regression analysis results are interesting, they show that if there is an association, it is likely not a straightforward one.…”
Section: Discussionmentioning
confidence: 98%
“…However, these 3 testing conditions varied not only in the method of presentation, but also in task format. It has been noted that blink rate decreases as font size and contrast are reduced (Gowrisankaran, Sheedy, & Hayes, 2007), or the cognitive demand of the task increases (Cardona, Garć ia, Serés, Vilaseca, & Gispets, 2011;Himebaugh, Begley, Bradley, & Wilkinson, 2009;Jansen, Begley, Himebaugh, & Port, 2010 observed by Tsubota and Nakamori may be related to changes in task difficulty, rather than being a consequence of changing from printed material to an electronic display. Indeed, a recent study in our laboratory compared blink rates when reading identical text from a desktop computer screen versus hardcopy printed materials (Chu, Rosenfield, & Portello, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…(Paradoxically, blinking is problematic for researchers monitoring blinking activity of experimental subjects, either directly or via video replays; in the latter case, viewing in slow motion solves this problem.) Volkmann et al 9 proposed that there is a suppression of the Blink frequency among contact lens wearers was found by Jansen et al 21 to be unaffected when concentrating on near tasks. The authors suggested that wearing soft contact lenses, even when fully adapted, provides enough extrinsic ocular surface stimulation to override internal controls and affect blink parameters.…”
Section: Purpose Of Blinkingmentioning
confidence: 96%